Southern Federal University in Relation to Teacher Education Modernization Project: Strategic Reflection of the Testing Results of Integrative Modules of the "Cultural-Historical Psychology and Activity Approach in Education" Research Master's Program - Chernaya A. V. (Moscow State University of Psychology and Education, 2015)
The article describes the experience of a strategic reflection of the Southern Federal University participation in the project of modernization of teacher education. It analyses how theoretical, methodological and organizational-activity basis of "Cultural-Historical Psychology and Activity Approach in Education" research master's program designed by Moscow State University of Psychology & Education relates to the strategic objectives of Southern Federal University. Priorities and forward-looking statements in the strategy for the training of specialists in education based on action-competence approach, integrative principle of educational modules construction, network forms of cooperation of educational institutions are shown. Basic methodological ideas of culturalhistorical psychology and activity theory and their applicability to the needs of modern education objectified in the draft are specially considered. The article presents the preliminary test results of integrative modules of research master's program for Southern Federal University